Deciphering the monomeric and dimeric conformational landscapes of the full-length TDP-43 and the impact of the C-terminal domain - Tammara, Vaishnavi; Doke, Abhilasha A.; Jha, Santosh Kumar; Das, Atanu (ACS Chemical Neuroscience, 2024)
The aberrant aggregation of TAR DNA-binding protein 43 kDa (TDP-43) in cells leads to the pathogenesis of multiple fatal neurodegenerative diseases. Decoding the proposed initial transition between its functional dimeric and aggregation-prone monomeric states can potentially design a viable therapeutic strategy, which is presently limited by the lack of structural detail of the full-length TDP-43. To achieve a complete understanding of such a delicate phase space, we employed a multiscale simulation approach that unearths numerous crucial features, broadly summarized in two categories: (1) state-independent features that involve inherent chain collapsibility, rugged polymorphic landscape dictated by the terminal domains, high beta-sheet propensity, structural integrity preserved by backbone-based intrachain hydrogen bonds and electrostatic forces, the prominence of the C-terminal domain in the intrachain cross-domain interfaces, and equal participation of hydrophobic and hydrophilic (charged and polar) residues in cross-domain interfaces; and (2) dimerization-modulated characteristics that encompass slower collapsing dynamics, restricted polymorphic landscape, the dominance of side chains in interchain hydrogen bonds, the appearance of the N-terminal domain in the dimer interface, and the prominence of hydrophilic (specifically polar) residues in interchain homo- and cross-domain interfaces. In our work, the ill-known C-terminal domain appears as the most crucial structure-dictating domain, which preferably populates a compact conformation with a high beta-sheet propensity in its isolated state stabilized by intrabackbone hydrogen bonds, and these signatures are comparatively faded in its integrated form. Validation of our simulated observables by a complementary spectroscopic approach on multiple counts ensures the robustness of the computationally predicted features of the TDP-43 aggregation landscape.
Keywords: chain collapsibility; domain-wisefluctuation; electrostatic dominance; hydrogen bond switchability; long-range crosstalk; persistent beta-character; protagonistic C-terminal domain; rugged phase space